(untitled) (Pedagogy of Higher and Secondary Education, 2004)
In the article are given modern principles of organization of the individual approach in the system of personal-oriented education of the teaches of music. The author investigates the content of principals of musical and general pedagogic, the ways of their realization in musical-performing preparing of the teacher of music in the secondary school. The author reveals the content of musical-performing preparing of the future teacher of music, which is organized on the basic of principals of professional-oriented education